Evaluasi dan Perbaikan Rancangan Pemesanan PCB Pada Situs Sfe-Electronics.com - Sanya Nabiela Nuraida; Ismiarta Aknuranda; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Printed Circuit Board (PCB) is one of the features available on the SFE-Electronics website. Recommended PCB ordering is expected to meet the needs of PCB buyers who can be ordered according to the needs of the buyer. However, in its application the PCB ordering feature has not been able to increase PCB bookings through the website. Of the total PCB sales only 6 out of 120 buyers make PCB order through the website. This study focuses on the evaluation and preparation of user interface design recommendations by adapting the Human-Centered Design (HCD) method. HCD is an approach method that incorporates a user's view of a system into the software development process to achieve a system that can be used as needed. Research begins with an initial evaluation conducted by identifying and analyzing stakeholders and understanding the user context and exploring the constraints of using PCB bookings. The second stage is to design the results of the first evaluation in which the results of the design is done further evaluation to find constraints on the design results. From the first evaluation stage found three obstacles on ordering PCB that is on aspect of user expectation, aspect of making of online form as ordering facility and participant response aspect. Nine pages of the design were made on the basis of the first evaluation results and from those nine outcomes were further evaluations that found obstacles on the PCB order page and automatic calculations which were then repeated.